Decreases of voltage-dependent K+ currents densities in ventricular myocytes of guinea pigs by chronic oxidant stress - DONG De-li; LIU Yan; ZHOU Yu-hong; SONG Wei-hua; WANG He; YANG Bao-feng (Acta Pharmacologica Sinica, 2016)
AIM: To determine the changes of delayed rectifier K(+) currents (I(k)) and inward rectifier K(+) currents (I(k1)) in the ventricular myocytes of guinea pigs during the gradual apoptotic process by the chronic oxidant stress treatment. METHODS: H(2)O(2) 50 micromol/L (24 h) was used for inducing apoptosis in the cardiomyocytes culture of neonatal rats and to treat the isolated ventricular myocytes of adult guinea pigs in vitro for 24 h. Apoptosis was evaluated by TUNEL methods and voltage-dependent K(+) currents were recorded by patch-clamp techniques. RESULTS: H(2)O(2) 50 micromol/L (24 h) induced cell apoptosis in the cardiomyocytes culture of neonatal rats. This concentration was used to treat the isolated ventricular myocytes of adult guinea pigs in vitro for 24 h and the voltage-dependent K(+) currents densities (I(k), I(k1)) were down-regulated. The densities of the delayed rectifier K(+) currents (I(k)) in 50 micromol/L H(2)O(2) group were 2.52+/-0.57 pA/pF vs 5.73+/-1.84 pA/pF in the control group at +50 mV (n=8, P